2015
DOI: 10.1080/15320383.2015.1029607
|View full text |Cite
|
Sign up to set email alerts
|

Mercury (II) Adsorption on Three Contrasting Chinese Soils Treated with Two Sources of Dissolved Organic Matter: II. Spectroscopic Characterization

Abstract: 2015): Mercury (II) adsorption on three contrasting Chinese soils treated with two sources of dissolved organic matter: II. AbstractTo reveal the influencing mechanism of dissolved organic matter (DOM) on mercury (Hg II) adsorption by black, red and fluvo-aquic soils in China, Fourier transform infrared (FTIR) spectroscopy, 13 C nuclear magnetic resonance (NMR) spectroscopy, and the 3-dimensional excitation emission matrix (3DEEM) fluorescence spectroscopy were employed to characterize the DOM samples and DOM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…4d), 44 implying the formation of the Hg-NOM complexes through the complexation between Hg and -COOH and/or -OH groups on the NOM molecules. [45][46][47] Additionally, the particle size and ζ potential of MoS 2 remained unaffected by the addition of NOM with concentration up to 100 mg L −1 (Fig. S14 †).…”
Section: Mechanism Of Hg Removal By Mos 2 In the Presence Of Nommentioning
confidence: 99%
“…4d), 44 implying the formation of the Hg-NOM complexes through the complexation between Hg and -COOH and/or -OH groups on the NOM molecules. [45][46][47] Additionally, the particle size and ζ potential of MoS 2 remained unaffected by the addition of NOM with concentration up to 100 mg L −1 (Fig. S14 †).…”
Section: Mechanism Of Hg Removal By Mos 2 In the Presence Of Nommentioning
confidence: 99%
“…3 and Table S2. Generally, DOM exerted good adsorption properties on environmental pollutants, particularly heavy metals (Ma et al 2015;Valipour et al 2018). With unique functional groups (i.e., carboxyl group and hydroxy group), DOM could become stable coupling with heavy metals (Chien et al 2021;Zhao et al 2018).…”
Section: Dom Participates In Enms-mediated Pollutants Removal Process...mentioning
confidence: 99%
“…Among various metal ions, copper ion (Cu 2+ ) [9][10][11] and mercury ion (Hg 2+ ) [12,13], were the most frequently investigated species. Previous studies demonstrated that binding constants between Cu 2+ , Hg 2+ , and NOM could be up to 10 6 L/mol [14,15], leading to a decreased fluorescence intensity of NOM.…”
Section: Introductionmentioning
confidence: 99%